Calcium Fertilizer Effect on Rhizopus Tuber Rot and Anthracnose Disease Caused by Colletotrichum Gloeosporioides in Dioscorea Rotundata Var. Efuru - Osijo, T. A.; Otusanya, M. O.; Enikuomehin, O. A.; Afolabi, C. G.; Olowokere, F. A. (European Journal of Applied Sciences, 2022)
The response of Dioscorea rotundata var Efuru, one of the popular white guinea yam varieties in South West Nigeria to calcium soil amendment for control of Rhizopus stolonifer.Ehrenb., tuber rot and Anthracnose disease caused by Colletotrichum gloeosporioides Penz. was investigated in this study. The field design was randomized complete block (RCBD) with three replicates.The mineral elements Calcium (Ca), Magnesium (Mg) and Potassium (K) in the soil of the experimental site were above the criticals reported for optimum yam production in South West Nigeria, but Nitrogen (N) and Phosphorus (P) were below. Soil amendment at 3MAP (months after planting) was with 0 kg ha-1 control, 3 kg ha-1 and 4 kg ha-1 Calcium from Calcium Nitrate. Anthracnose severity was not significantly different across treatments in any of the four periods of assessment. Severity score was resistant (1.00) at 4MAP, resistant (1.22) at 5MAP moderately resistant (2.00) at 6MAP, but moderately susceptible (2.89) at 7MAP.This implies that variety Efuru is susceptible late in the growth cycle. Future trials may accommodate additional (in addition to the 3MAP calcium soil amendment), calcium nitrate foliar spray at 6MAP and 7MAP with trial doses less than 100 mgl-1, as is reported for D. alata var. Alakisa, for reduction of anthracnose severity to resistant level. Shoot number per plant, mean values 2.45 and 2.71 at 4MAP and 6MAP respectively, were not significantly different across treatments. Shoot length at 4MAP (309.58cm) was significantly higher in the 4 kg ha-1 treatment than the control (277.80cm), but was similar across treatments at 6MAP. Mean tuber number per plant at 8MAP was similar across treatments and had overall mean of 2.39. Tuber yield at 8MAP, which was similar across treatments was the equivalent of 31.50 tons ha-1 (control), 30.10 tons ha-1 (3 kg ha-1) and 35.70 tons ha-1 (4 kg ha-1), which is similar to 34.20tons ha-1 reported as optimum for economic production of white guinea yam in South West Nigeria. Yield obtained in this study may be due to firstly Ca, Mg and K being above critical for optimum yam production in the soil site. And secondly even though N and P were below critical, N was supplied from the fertilizer and the requirement for P was invariably taken care of by the mycorrhizal associations of the roots. Tubers inoculated at 6MAP for 4 weeks with Rhizopus stolonifer were similar across treatments in infection (mean 1.37%) and weight loss (mean 16.88%). Infection in tubers inoculated at 8MAP for 4 weeks was high, that is 48.79% in the control, significantly higher than the 3kg ha-1treatment which was 0.57%, which was in turn higher than the 0.61 % of the 4 kg ha -1treatment. Mean infection of 0.59% in the two calcium treatments is a reduction of 98% of infection in the control. Thus3kg ha-1 and 4 kg ha -1 calciun soil amendment are appropriate for R. stolonifer rot control in Dioscorea rotundata var. Efuru. However, 3 kg ha-1 calcium soil amendment is to be preferred as it gave lower infection.Weight loss at 6MAP and 8MAP, overall means of 16.88% and 2.39% respectively were similar across treatments. Weight loss of 2% at 8MAP in the two calcium treatments is a reduction of over 88% of mean weight loss of 17.33% of the two treatments at 6MAP. Crude fibre and fat were higher in tubers of the calcium-fertilized plants than the control, but crude protein, ash and carbohydrate were higher in control tubers. Ca, Mg, K, Fe and Zn were higher in the calcium-treated plant tubers than the control but Mn and Cu were higher in the control. Calcium fertilization improved accumulation/acquisition of four of the seven mineral elements reported to be often lacking in human diets that is Ca, Mg, Fe and Zn, in Dioscorea rotundata var. Efuru tubers.